Effect of Covid-19 on Small Scale Industries with Reference to Ernakulam District - et. al., Shubha Menon, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In India the current scenario is such that service sector contributes to the major portion of the GPD 54.77%1, which includes small and midcap companies. The Small Scale Industrial sector is the second biggest contributor with 27.47%. Thus in this paper an attempt is made to study what are the difficulties the small scale industrial sector in Ernakulam district had to face during this COVID-19 pandemic and whether The Atma Nirbhar Bharat Abhiyan was able to provide ample support to this sector. The major source of information was collected from secondary data. The limited primary data received from the manufacturers in Ernakulam district validate that the pandemic has effected them adversely and also that most of the industrialist had little idea about Atma Nirbhar Bharat Abhiyan.